The pitch glide speech task lacks clinical utility to infer laryngeal lift during swallowing†. - Kennedy, Samantha; Pisegna, Jessica M.; Kim, Kaylee; Parker, Linda; Langmore, Susan (International Journal of Speech-Language Pathology, 2020)
Purpose: To investigate the amount of laryngeal lift during the pitch glide speech task and during a bolus swallow. Method: Modified Barium Swallows (MBS) videos captured speech tasks and bolus trials. Using SwallowTail®, laryngeal elevation was measured by the amount of laryngeal lift from rest to its maximum excursion during each subject's pitch glide and 5 mL thin liquid, 20 mL thin liquid, and 15 mL puree trials. Paired t-tests, with Bonferroni correction, determined if there was a difference in laryngeal lift between the pitch glide and the bolus trials. Two methods were used to compare the methodology of measuring laryngeal lift. Result: Each subject's pitch glide was compared to their swallows. Laryngeal lift during the bolus swallow was greater than the lift during the pitch glide by an average of 1.10 cm, 1.38 cm, and 1.34 cm for 5 mL thin liquid, 20 mL thin liquid, and 15 mL puree, respectively. There was a significant difference in laryngeal lift between the pitch glide task and the 20 mL thin liquid, 5 mL thin liquid, and 15 mL puree swallows. Measurement tracking the posterior cricoid detected greater differences than the previous methodology using the hyoid. Conclusion: In this group of dysphagic patients, the larynx lifted significantly less during a pitch glide than during bolus swallows.